Clinical and hematologic aspects of the X-linked alpha-thalassemia/mental retardation syndrome (ATR-X). - Gibbons, R; Brueton, L; Buckle, V; Burn, J; Clayton-Smith, J; Davison, B; Gardner, R; Homfray, T; Kearney, L; Kingston, H (1995)
The hallmarks of the X-linked alpha-thalassemia/mental retardation (ATR-X) syndrome are severe psychomotor retardation, minor facial anomalies, genital abnormalities, and an unusual form of alpha-thalassemia. The demonstration of HbH inclusions in red blood cells after incubation with brilliant cresyl blue confirms the diagnosis. We describe 15 previously unreported cases and analyse the phenotypic and hematologic findings in these subjects and compare them with previously published cases. This study demonstrates the consistency of the main characteristics of this syndrome and extends the phenotype. Developmental changes in phenotype, in particular the coarsening of the facial appearance, are illustrated. The hematologic findings are shown to vary widely; in some cases the manifestation of alpha-thalassemia may be subtle and missed without repeated examination.